Shear bond strength of metal-ceramic repair systems - Santos, Juliana Gomes dos; Fonseca, Renata Garcia [UNESP]; Adabo, Gelson Luis [UNESP]; Santos Cruz, Carlos Alberto dos (Mosby, Inc, 2006)
Statement of problem. When clinical fractures of the ceramic veneer on metal-ceramic prostheses can be repaired, the need for remake may be eliminated or postponed. Many different ceramic repair materials are available, and bond strength data are necessary for predicting the success of a given repair system.Purpose. This study evaluated the shear bond strength of different repair systems for metal-ceramic restorations applied on metal and porcelain.Material and methods. Fifty cylindrical specimens (9 X 3 mm) were fabricated in a nickel-chromium alloy (Vera Bond 11) and 50 in feldspathic porcelain (Noritakc). Metal (M) and porcelain (P) specimens were embedded in a polyvinyl chloride (PVC) ring and received I of the following bonding and resin composite repair systems (n=10): Clearfil SE Bond/Clearfil AP-X (CL), Bistite II DC/Palfique (BT), Cojet Sand/Z100 (Q), Scotchbond Multipurpose Plus/Z100 (SB) (control group), or Cojet Sand plus Scotchbond Multipurpose Plus/Z100 (CJSB). The specimens were stored in distilled water for 24 hours at 37 degrees C, thermal cycled (1000 cycles at 5 degrees C to 55 degrees C), and stored at 37 degrees C for 8 days. Shear bond tests between the metal or ceramic specimens and repair systems were performed in a mechanical testing machine with a crosshead speed of 0.5 mm/min. Mean shear bond strength values (MPa) were submitted to 1-way ANOVA and Tukey honestly significant difference tests (alpha=.05). Each specimen was examined under a stereoscopic lens with X 30 magnification, and mode of failure was classified as adhesive, cohesive, or a combination.Results. on metal, the mean shear bond strength values for the groups were as follows: MCL, 18.40 +/- 2.88(b); MBT, 8.57 +/- 1.00(d); MCJ, 25.24 +/- 3.46(a); MSB, 16.26 +/- 3.09(bc); and MCJSB, 13.11 +/- 1.24(c). on porcelain, the mean shear bond strength values ofeach group were as follows: PCL, 16.91 +/- 2.22(b); PBT, 18.04 +/- 3.2(ab); PCJ, 19.54 +/- 3.77(ab); PSB, 21.05 +/- 3.22(a); and PCJSB, 16.18 +/- 1.71(b). Within each substrate, identical superscript letters denote no significant differences among groups.Conclusions. The bond strength for the metal substrate was significantly higher using the Q system. For porcelain, SB, Q, and BT systems showed the highest shear bond strength values, and only SB was significantly different compared to CL and CJSB (P <.05).